Review on The Application for Rights Juridical Backing to Book C Village Based on PP No 24 of 1997 on Land Registration in Sumowono Sub-District, Semarang District - Rina Budi Setiyani; Dhanar Dhono Vernandhie; Djauhari Djauhari (Jurnal Akta, 2019)
Land registration function is to provide evidence of land ownership (certificate) in order to provide legal certainty and legal protection to rights holders on the ground. PP 24/1997 on land registration, implying that the Certificate of Land Rights to provide legal protection to the rights holder named on the certificate as evidence that stronger as the physical data, juridical met. In corvetion indigenous lands and quotation Village Books C that is Letter C which may be cited as proof of entitlement. Letter C contains data on the origin of the soil and record the transition that occurs before 24 September 1960. In the PP 24/1997 states that the book excerpts C Letter C Village and Village serves as evidence of payment of tax and have the force of law as the foundation of evidence for the right to land. Village C book loss events resulted in the loss of certainty about the object, the subject, and the certainty of the status of their land rights and it can cause problems to the strength of evidence for the right to land. Then how the impact of the loss of the book C Village of the rights on public land that is lost letter C? ensuring legal certainty for holders of indigenous land rights and land registration application process for them.The research method of juridical empirical approach to socio-legal research, by location in District Sumowono and Semarang District Land Office.Keywords: Land Registration, Guarantee Legal Certainty, The Strength Of Evidence.